Do Plaques Rapidly Progress Prior to Myocardial Infarction?: The Interplay Between Plaque Vulnerability and Progression. Issue 1 (19th June 2015) - Ahmadi, Amir; Leipsic, Jonathon; Blankstein, Ron; Taylor, Carolyn; Hecht, Harvey; Stone, Gregg W.; Narula, Jagat
Abstract : There is a common misperception in the cardiology community that most acute coronary events arise from ruptures of mildly stenotic plaques. This notion has emanated from multiple studies that had measured the degree of angiographic luminal narrowing in culprit plaques months to years before myocardial infarction. However, angiographic studies within 3 months before myocardial infarction, immediately after myocardial infarction with thrombus aspiration or fibrinolytic therapy, and postmortem pathological observations have all shown that culprit plaques in acute myocardial infarction are severely stenotic. Serial angiographic studies also have demonstrated a sudden rapid lesion progression before most cases of acute coronary syndromes. The possible mechanisms for such rapid plaque progression and consequent luminal obstruction include recurrent plaque rupture and healing and intraplaque neovascularization and hemorrhage with deposition of erythrocyte-derived free cholesterol. Moreover, recent intravascular and noninvasive imaging studies have demonstrated that plaques which result in coronary events have larger plaque volume and necrotic core size with greater positive vessel remodeling compared with plaques, which remain asymptomatic during several years follow-up, although these large atheromatous vulnerable plaques may angiographically seem mild. As such, it is these vulnerable plaques which are more prone to rapid plaque progression or are those in which plaque progression is more likely to become clinically evident. Therefore, in addition to characterizing plaque morphology, inflammatory activity, and severity, detection of the rate of plaque progression might identify vulnerable plaques with an increased potential for adverse outcomes.